Parent/carer views about deferred consent in trials of emergency treatments in children with life-threatening illness. (29th September 2015) - Nadel, S; Young, B; Gamble, C; Hickey, H; Williamson, P; Snape, D; Snowden, C; Glennie, L
Abstract : Introduction: Obtaining informed consent for studies of emergency treatments in children with acute life-threatening illness is difficult and may preclude vital clinical trials. Aims: To investigate parents' views regarding consent in a hypothetical emergency resuscitation trial comparing two treatments which are in widespread use, and considered safe in children with sepsis. Methods: Postal questionnaire survey. Parents were presented with a scenario describing the trial in two parts: (1) Would parents want to be informed about the trial at the time of resuscitation, or would they want to be included and then informed after their child's condition had stabilised, or not informed at all about the trial? (2) How would parents approach a scenario where a child had been included without prior consent, but the child died before the parents were informed about the trial? Participants were all members of Meningitis Research Foundation with a child affected by bacterial meningitis (BM) or meningococcal septicaemia (MS) within the previous 5 years. The study aimed to include a representative sample from families who had been bereaved due to BM/MS. Results: 220 families were sent questionnaires (63 bereaved); 68 (31%) responded (equal proportions from bereaved families as from survivors). Three respondents would not want their child included under any circumstances, and 30% would not have wanted inclusion before the trial was explained to them. The principle of deferred consent was acceptable to 66% of respondents; however 33% would not want to be told about the trial at any stage. If the child had died, 51% of respondents did not think it appropriate to inform the parents that their child had been entered into a trial. More bereaved respondents would have wanted to be told about the study at some stage (66% vs 37%, p=0.06). Conclusion: The majority of parents indicated acceptance of a child's inclusion into emergency treatment trials without prior informed consent. Efforts to inform families and deferred consent may be acceptable in certain circumstances. Trials of emergency treatments in children are vital, but logistically difficult. The contribution of our findings to the implementation of emergency therapeutic studies will be discussed.